2023
DOI: 10.3389/fimmu.2023.1240262
|View full text |Cite
|
Sign up to set email alerts
|

Dupilumab improve acquired reactive perforating collagenosis characterized by type 2 inflammation

Ben Liu,
Yibei Wu,
Xiaoyan Wu
et al.

Abstract: BackgroundAcquired reactive perforating collagenosis (ARPC) is a clinically challenging disease with an unclear pathogenesis.ObjectiveTo evaluate the efficacy and safety of dupilumab for the treatment of ARPC, and analyze the expression of type 2 inflammation-related molecules in ARPC lesions.MethodsThis retrospective cohort study included 20 patients with ARPC; 10 received dupilumab and 10 received conventional therapy. The efficacy and safety of dupilumab were evaluated at 12 weeks. Immunohistochemical and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In a retrospective cohort study, predominance of T helper 2 cells and the upregulated cytokines IL-4 and IL-13 were observed in ARPC, indicating the involvement of the T helper 2 axis immune response in its pathogenesis. 1 Given that the Janus kinase/signal transducers and activator of transcription signal mediates T helper 2 cytokines, regulates the epidermal barrier, and modulates peripheral nerves of pruritus transduction, 8 upadacitinib should be a promising potential therapy for refractory ARPC, despite the limitation of a single case report.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective cohort study, predominance of T helper 2 cells and the upregulated cytokines IL-4 and IL-13 were observed in ARPC, indicating the involvement of the T helper 2 axis immune response in its pathogenesis. 1 Given that the Janus kinase/signal transducers and activator of transcription signal mediates T helper 2 cytokines, regulates the epidermal barrier, and modulates peripheral nerves of pruritus transduction, 8 upadacitinib should be a promising potential therapy for refractory ARPC, despite the limitation of a single case report.…”
Section: Discussionmentioning
confidence: 99%
“…Treatments including topical steroids, oral antihistamines, allopurinol, UV-B phototherapy, and dupilumab have been reported as effective but can be unpredictable. 1 …”
Section: Introductionmentioning
confidence: 99%
“… 7 Liu et al found enhanced dermal infiltration of CD3 + T-cells with a predominance of Th2 cells. 8 In addition, the cytokines interleukin (IL)-4 and IL-13 were also significantly upregulated in RPC. 8 …”
Section: Discussionmentioning
confidence: 99%
“… 8 In addition, the cytokines interleukin (IL)-4 and IL-13 were also significantly upregulated in RPC. 8 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation